Pelatihan soft skill sebagai strategi eskalasi promosi UMKM di desa eko–eduwisata Kandri dan Jatirejo, Kecamatan Gunungpati, Kota Semarang - William Ben Gunawan; Monica Rachmani (University of Muhammadiyah Malang, 2022)
Jatirejo Village has the potential to become a tourist village because of its attraction as a Kolang-Kaling Processed Village (Kokolaka) and has a River Tubing Topongeli tour. On the other hand, Kandri Village also has tourist attractions such as Kreo Cave and Jatibarang Reservoir. The skill of making promotional media designs and compiling reports on business activities is important in a tourist village. Therefore, Diponegoro University students are interested in holding a service with the title